Distribution of Inheritance According To Gender Equality Approach (Comparative Study of Tafsir Quraish Shihab and Aminah Wadud) - Siti Safhira Faradilla (Jurnal Indonesia Sosial Teknologi, 2024)
The division of inheritance 2 1 is the final division in the Qur'an. The author compares contemporary Muslim feminist and contemporary interpretations of thought, namely the modern interpretation of Al-Misbah by Quraish Shihab and Amina Wadud's method of thought. Both are well-known figures in their circles. The research method used is library research (library research), with data processing techniques used comparative methods. This article compares the thoughts of Qurais Shihab and Amina Wadud. In the interpretation of Al-Misbah, the division of inheritance 2:1 cannot be changed; this is a final decision already made with provisions in the Qur'an. However, another work of Quraish Shihab allows a 1:1 division, but with the condition that the heirs (such) agree. Meanwhile, according to Amina Wadud, the distribution of inheritance 2 1 is not a final division, but this is one of the various ways of dividing inheritance. Amina Wadud saw the size of the benefits of the heirs. The heirs will get 1:1 if each is equally useful and fair for both heirs. From the division of inheritance according to the two figures, it turns out that gender equality has been fulfilled. These two figures provide access, participation, and benefits to the heirs getting their respective shares.